Do children who exhibit food selectivity prefer to save the best (bite) for last?. (23rd November 2021) - Borrero, John C.; Rosenblum, Amy K.; Castillo, Mariana I.; Spann, Matthew W.; Borrero, Carrie S. W.
Abstract: Preference for patterns of outcomes that improve over time is termed negative time preference, in economics. In lay terms, this concept equates to "saving the best for last." Generally, adults tend to prefer to postpone their more preferred outcomes when options are presented as a sequence of events. Event sequencing seems particularly relevant for children who exhibit food refusal or selectivity. Preference for the sequencing of bites when an array involved preferred and relatively non‐preferred foods was evaluated. Participants experienced pre‐programed bite sequences that improved, worsened, or remained fixed across trials, and we assessed participants' preference for each of the bite sequences. Three of the four participants preferred bite sequences that began with a highly preferred food and either worsened or remained fixed over time, whereas one participant preferred the improving sequence of bite presentation, or in other words, one participant preferred to "save the best for last."